Comparison of clinical indications and postoperative histopathological diagnoses of hysterectomy specimens with benign preliminary diagnoses - Bozdag, Zehra; Faruk Dizibuyuk, Omer; Bayramoglu Tepe, Neslihan (Annals of Medical Research, 2021)
None